Educating in ethics across the professions : a compendium of research, theory, practice, and an agenda for the future - Jacobs, Richard M. (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
Educating in Ethics for the Professions: A Compendium of Research, Theory, Practice, and an Agenda for the Future offers a state-of-the-art discussion on the part of applied ('professional') ethics educators who describe the teaching of ethics for their professions and who collectively represent a wide-ranging array of professions.The volume begins with an overview of the topics, contested ideas, and challenges confronting applied ethics educators, across the generations, providing a foundation from which the concept of ethics education as an integral formation frames each contributor's historical overview identifying how research, theory, and practice have evolved in each profession to this day. These discussions then turn to the topics, contested ideas, and challenges emerging in contemporary discourse. Each discussion culminates with suggestions regarding what ethics educators must consider for the future. The volume closes with a synthesis of the commonalities among and differences between the discussions representing diverse professional perspectives, yet framing this history as well as identifying an agenda for teaching applied ethics in the future.
Keywords: Professional ethics -- Study and teaching.; Business & Economics -- Business Ethics.; Ethics and moral philosophy.; Business ethics and social responsibility.; elektronické knihy; electronic books